PELAYANAN INFORMASI OBAT PADA TENAGA VOKASI KEFARMASIAN DI APOTEK KESHIA FARMA - Rosita Surbakti; Julini Paradit; Nilta Sibayang; Anggita4 Anggita (SUAN PUBLISHER, 2025)
This study aims to evaluate the quality of Drug Information Services (DIO) provided by vocational pharmacy personnel (Pharmacy Assistants/Pharmacy Technical Personnel) at Keshia Farma Pharmacy. Accurate, comprehensive, and easy-to-understand DIO is crucial to ensure rational and optimal drug use by patients. The research method used is descriptive qualitative, with data collection through direct observation, in-depth interviews with vocational pharmacy personnel, and patient simulations to assess DIO responses in various scenarios. The data is also supplemented with a review of standard operating procedure (SOP) DIO documents at Keshia Farma Pharmacy. Data analysis was carried out using triangulation techniques to compare information from various sources. The expected results show a comprehensive picture of the level of knowledge of vocational personnel, communication skills, and the availability of drug information sources used. Potential obstacles in the implementation of DIO, such as workload or lack of ongoing training, will also be identified. This study is expected to provide valuable input for Keshia Farma Pharmacy in improving the quality of DIO, which ultimately contributes to increasing patient safety and compliance in drug use.